Diversity of MIS 3 Levallois technology from Motravulapadu, Andhra Pradesh, India‐implications of MIS 3 cultural diversity in South Asia - Anil, Devara; Devi, Monika; Ati, Neha; C. P, Mukesh; Khan, Zakir; Mahesh, Vrushab; Ajithprasad, P.; Chauhan, Naveen; Pandey, Akash; Jha, Gopesh (Frontiers in Earth Science, 2023)
The chronology and hominin association of the South Asian Middle Palaeolithic have attracted much attention in the last few decades. The emergence of Middle Palaeolithic culture in the region has been debated between the local origins (behavioural change) model based on an early date around 380 ka and the diffusion (biological change) model based on Homo sapiens dispersals from Africa around 120–80 ka. The latter has more consensus, whereas the former requires a more robust chronological framework to attribute the emergence of the Middle Palaeolithic to behavioural changes. In the absence of hominin remains, the presence of Middle Palaeolithic technological trajectories are frequently used as behavioural markers of Homo sapiens. Homo sapiens fossil remains from the regions between Africa and South Asia dated to ⁓ 200 ka presents more convincing support for the latter model. Here we present contextual, chronological and technological analysis of Middle Palaeolithic assemblages dated to 52 ka from Motravulapadu, Andhra Pradesh, India. Morphometrical analysis of the lithic assemblage indicates diverse Levallois core reductions were practised at the site at the onset of MIS 3. Further this evidence highlights the significance of MIS 3 cultural diversity in South Asia, likely related to changing population dynamics, cultural drift, and the highly variable climatic context of MIS 3.